The Evidence for Altered BDNF Expression in the Brain of Rats Reared or Housed in Social Isolation: A Systematic Review - Murínová, Jana; Hlaváčová, Nataša; Chmelová, Magdaléna; Riečanský, Igor (Frontiers in Behavioral Neuroscience, 2017)
There is evidence that development and maintenance of neural connections are disrupted in major mental disorders, which indicates that neurotrophic factors could play a critical role in their pathogenesis. Stress is a well-established risk factor for psychopathology and recent research suggests that disrupted signaling via brain-derived neurotrophic factor (BDNF) may be involved in mediating the negative effects of stress on the brain. Social isolation of rats elicits chronic stress and is widely used as an animal model of mental disorders such as schizophrenia and depression. We carried out a systematic search of published studies to review current evidence for an altered expression of BDNF in the brain of rats reared or housed social isolation. Across all age groups (postweaning, adolescent, adult), majority of the identified studies (16/21) reported a decreased expression of BDNF in the hippocampus. There are far less published data on BDNF expression in other brain regions. Data are also scarce to assess the behavioral changes as a function of BDNF expression, but the downregulation of BDNF seems to be associated with increased anxiety-like symptoms. The reviewed data generally support the putative involvement of BDNF in the pathogenesis of stress-related mental illness. However, the mechanisms linking chronic social isolation, BDNF expression and the elicited behavioral alterations are currently unknown.